Isoniazid - induced chronic cutaneous Lupus erythematosus - Chiriac, A; Brzezinski, P; Chiriac, A E; Foia, L; Mihaila, D; Solovan, C (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
A 23-year-old man developed drug-induced chronic cutaneous lupus erythematosus 8 months after isoniazid (INH) therapy for pulmonary tuberculosis. Diagnosis was based on clinical aspects (discoid lesions on the face, erythema, photosensitivity, hyperpigmentation), histopathological examination, along with direct immunofluorescence examination (DIF), the absence of systemic involvement and the routine laboratory parameters, which registered all within normal range. Hydroxychloroquine therapy associated to photo protection and emollients determined the clear up of the facial eruption within six months. Transient residual hyperpigmentation could be noticed 2 months after discontinuation of the treatment. This case illustrates a rare form of drug-induced chronic cutaneous lupus erythematosus developed 2 months after withdrawal of antituberculosis therapy, with excellent results with hydroxychloroquine. NJDVL Vol. 13, No. 1, 2015 Page: 52-56